Aufeis thickness and volume estimations from stereo satellite imagery and terrestrial photographs: evidence from Central Ladakh, India - Brombierstäudl, Dagmar; Schmidt, Susanne; Soheb, Mohd; Nüsser, Marcus (The science of the total environment, 2024)
Aufeis - a phenomenon associated with permafrost and the cold arid region of Ladakh - serves as a critical water resource for local communities. In several tributaries of the Indus River, aufeis accumulation is enhanced in ice reservoirs (commonly known as “artificial glaciers”) to store winter baseflow for crop irrigation during the water-scarce period in spring. This study investigates aufeis thickness and volume across four study sites in the Trans-Himalaya of Central Ladakh: the ice reservoirs of Phuktse and Igoo and the catchments of Gya and Sasoma, where natural aufeis fields occur. Aufeis thickness and volume estimates were derived via differencing of digital elevation models calculated from very high-resolution stereo Pléiades imagery and terrestrial photographs. The study revealed ice thickness up to a maximum of 3 m and could further demonstrate the amplification effect of the walls of the ice reservoirs on aufeis accumulation in both, differenced elevation from Pléiades and terrestrial photographs. Aufeis volumes across the four study sites range from 34,106 ± 13,440 m3 in Phuktse up to 105,790 ± 28,511 m3 in Sasoma, indicating substantial amounts that need to be considered in future hydrological studies in the region. While the approach with terrestrial photographs is especially suitable for local studies, the results from very high-resolution stereo satellite data are promising for aufeis studies on large spatial scales. It represents an important contribution for the understanding of spatial aufeis patterns in the Trans-Himalaya and affected regions worldwide.